2018
DOI: 10.1075/ttmc.00019.all
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal visually-oriented translanguaging among Deaf signers

Abstract: Translanguaging is often regarded with great skepticism in the context of Deaf education, as an approach that has already been tried, with disastrous results. Already in the 1960’s educators understood the critical importance of allowing deaf children to exploit their full linguistic repertoire for learning: not only listening, lip-reading and reading/writing, but also sign language, fingerspelling, gesture, and other strategies that render language visually accessible. The resulting teaching philosophy, Total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In the context of sign languages and deaf education settings, the translanguaging concept has been used to describe bilingual or multilingual pedagogies (Allard and Chen Pichler 2018;García 2009; García and Cole 2014; Holmström and Schönström 2018; Lewis, Jones, and Baker 2012; Swanwick 2017). It has also been used as a framework to describe and/or theorise deaf people's languaging practices in translation projects, shops and markets, village settings, theatre productions, deaf organisations, and language classes for hearing parents (Kusters 2017a; Moriarty Harrelson 2017; Murray 2017; Robinson 2017; Safar 2017; Snoddon 2017).…”
Section: Sensorial Asymmetriesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of sign languages and deaf education settings, the translanguaging concept has been used to describe bilingual or multilingual pedagogies (Allard and Chen Pichler 2018;García 2009; García and Cole 2014; Holmström and Schönström 2018; Lewis, Jones, and Baker 2012; Swanwick 2017). It has also been used as a framework to describe and/or theorise deaf people's languaging practices in translation projects, shops and markets, village settings, theatre productions, deaf organisations, and language classes for hearing parents (Kusters 2017a; Moriarty Harrelson 2017; Murray 2017; Robinson 2017; Safar 2017; Snoddon 2017).…”
Section: Sensorial Asymmetriesmentioning
confidence: 99%
“…A prescriptive use of translanguaging, namely seeing all multimodal communication as equally accessible, or emancipating, overlooks sensorial asymmetries and differential access to semiotic resources but also and crucially, might threaten the vitality and maintenance of sign languages as minority languages. Translanguaging as an idealised pedagogical approach also has risks, given that the majority of teachers teaching deaf students are not proficient in a sign language (Allard and Chen Pichler 2018).…”
Section: Sensorial Asymmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of these structures is modulated by language dominance as well as context. This view is reminiscent of translanguaging, an approach recently expanded to sign language applications (Allard & Chen Pichler, 2018). Holmström and Schönström (2017) use a translanguaging analysis to reveal richly multilingual strategies of a skilled deaf lecturer teaching a university‐level course in Sweden to mixed hearing and deaf students that integrates not only multiple sign languages but also languages in written and spoken form through mouthing and borrowed spoken language terminology.…”
Section: Modality Effects As Bimodal Phenomena That Occur When Langua...mentioning
confidence: 99%
“…Through classroom observation records, the author found that English classes in colleges and universities are characterized by dogmatization and homogenization [ 6 ]. For example, in one of the classes observed by the author, the teacher first explained new words and introduced relevant background information, then translated and analyzed the text word by word and explained grammar; students were passively listening and taking notes [ 7 ]. The teacher did not give students the opportunity to practice speaking and daily communication in the classroom.…”
Section: Introductionmentioning
confidence: 99%